(3GdeWdH aj GdYed HGdQHY GdeLjHs - (3eMeO Hf eMeO Hf CMeO GdZRGd GdOeTbqj, HOQ GdOjf, GdTgjQ HSHW GdeGQOjfj , J (B912 (3g` s ((3YHO Gddg Hf YHO GdSdGe GdOejGWi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi JbOSJ ai LeGd UaGJg YeG jNWQ ai GdChgGe s
(3BNQgG (B:s
(3JeJ HMeO Gddg hYhfg hMSf Jhajbgq s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B54 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B188s
Keywords: (3Gdadcs